Microservices Architecture Enables DevOps: Migration to a Cloud-Native Architecture - Balalaie, Armin; Heydarnoori, Abbas; Jamshidi, Pooyan (IEEE software, 2016)
This article reports on experiences and lessons learned during incremental migration and architectural refactoring of a commercial mobile back end as a service to microservices architecture. It explains how the researchers adopted DevOps and how this facilitated a smooth migration.